The demographic transformation of post-socialist countries - Elizabeth Brainerd (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The formerly socialist countries of Eastern Europe and the former Soviet Union have experienced a remarkable demographic transformation in the past twenty years. On many dimensions of fertility and family formation, much of the region now looks like Western Europe-below-replacement fertility rates, rising age at first marriage and first birth, and high and increasing out-of-wedlock birthrates, characterize many countries formerly distinguished by replacement-level fertility and early, near-universal marriage and childbearing. The other facet of this demographic transformation is nearly unprecedented changes in adult mortality rates. An upsurge of cardiovascular and external cause mortality caused a massive premature loss of life among working-age men in the former Soviet Union in the 1990s. In contrast, cardiovascular mortality has fallen at a rapid rate across Eastern Europe since 1989. This study discusses the dimensions and most likely causes of these demographic changes and assesses the possible consequences of the changing fertility and mortality patterns. Much remains unknown about the underlying reasons for the demographic transformation of the region; directions for future research in this area are discussed.
Keywords: J11; J13; P36; 330; fertility; marriage; mortality; transitional economies; Fruchtbarkeit; Ehe; Sterblichkeit; Demographie; Übergangswirtschaft; Osteuropa